Decoupling and Reprogramming the Wiggling Motion of Midge Larvae Using a Soft Robotic Platform. Issue 17 (18th March 2022) - Xia, Neng; Jin, Bowen; Jin, Dongdong; Yang, Zhengxin; Pan, Chengfeng; Wang, Qianqian; Ji, Fengtong; Iacovacci, Veronica; Majidi, Carmel; Ding, Yang; Zhang, Li
Abstract: The efficient motility of invertebrates helps them survive under evolutionary pressures. Reconstructing the locomotion of invertebrates and decoupling the influence of individual basic motion are crucial for understanding their underlying mechanisms, which, however, generally remain a challenge due to the complexity of locomotion gaits. Herein, a magnetic soft robot to reproduce midge larva's key natural swimming gaits is developed, and the coupling effect between body curling and rotation on motility is investigated. Through the authors' systematically decoupling studies using programmed magnetic field inputs, the soft robot (named LarvaBot) experiences various coupled gaits, including biomimetic side‐to‐side flexures, and unveils that the optimal rotation amplitude and the synchronization of curling and rotation greatly enhance its motility. The LarvaBot achieves fast locomotion and upstream capability at the moderate Reynolds number regime. The soft robotics‐based platform provides new insight to decouple complex biological locomotion, and design programmed swimming gaits for the fast locomotion of soft‐bodied swimmers. Abstract : A magnetic soft robotic platform to decouple and reprogram complex wiggling motion adopted by invertebrates is presented. By using magnetic soft robot and programmed magnetic field inputs, it is unveiled that the synchronization of body curling and rotation, and the optimal rotation amplitude greatly enhance motility. The robotic platform offers a new toolbox to develop optimized soft‐bodied swimmers with enhanced motility.